Polyacrylamide Polymer Gel Systems for Conformance Control Technology: A Review - Al-delfi, Ali; Al-Mahdawi, Faleh H. M. (Iraqi Journal of Chemical and Petroleum Engineering, 2022)
Low oil extraction and early high water production are caused in part by reservoir heterogeneity. Huge quantities of water production are prevalent issues that happen in older reservoirs. Polyacrylamide polymer gel systems have been frequently employed as plugging agents in heterogeneous reservoirs to regulate water output and increase sweep efficiency. Polyacrylamide polymer gel systems are classified into three classes depending on their composition and application conditions, which are in-situ monomer gel, in-situ polymer gel, and preformed particle gel (PPG). This paper gives a comprehensive review of PPG’s status, preparation, and mechanisms. Many sorts of PPGs are categorized, for example, millimeter-sized preformed particle gels, microgels, pH-sensitive cross-linked polymers, swelling polymer grains, and Bright Water®. In addition to this, the most important factors to consider while assessing gel performance, such as swelling capacity, PPG injectivity, and plugging efficiency, are studied carefully. Not only are the design considerations and field application of PPG mentioned, but also the advantages of PPG are demonstrated. Gels have been used in around 10,000 wells worldwide to reduce the fractures permeability or super-high permeability channels during water and polymer floods.